Synthesis of 1, 2‐Diaryl‐ and 1‐Aryl‐2‐alkylimidazoles with Sterically Demanding Substituents. Issue 27 (31st July 2013) - Micksch, Maik; Tenne, Mario; Strassner, Thomas
Abstract: 1, 2‐Diarylimidazoles are an important class of compounds. They are frequently used as ligands for photophysically active metal complexes and also display physiological activity. We developed a new, high‐yielding procedure for the synthesis of 1, 2‐diaryl‐substituted imidazoles with sterically demanding substituents at the respective ortho positions by starting from commercially available anilines and benzoic acids through the corresponding acid chlorides. The metal‐free method provides access to a variety of different substituents on the phenyl rings at N‐1 and C‐2 as well as at the 4, 5‐positions of the imidazole backbone. Our new method is also suitable for the preparation of 1‐aryl‐2‐alkylimidazoles. Abstract : A high‐yielding, metal‐free procedure is described for the synthesis of 1, 2‐diarylimidazoles with sterically demanding substituents. This procedure allows for the variation of groups at the N‐1 and C‐2 positions of the imidazole ring and starts from inexpensive anilines and carboxylic acids. Because the method is highly versatile, 1‐aryl‐2‐alkylimidazoles could also be prepared.